PENYELESAIAN SENGKETA TANAH DI DESA GUNUNGSARI MELALUI MEDIASI BERDASARKAN UNDANG-UNDANG NOMOR 30 TAHUN 1999 TENTANG ALTERNATIF PENYELESAIAN SENGKETA DAN ARBITRASE - Primasari, Imas Khaeriyah; Alpiyah, Nur (Universitas Wiralodra, 2024)
This research discusses the problem of land disputes in Gunungsari village between Mr. Sukasa and Mr. Ari, in which Mr. Ari claimed ownership of land from Mr. Sukasa and resulted in a land dispute. The specification of this research is Descriptive Law with a Normative Juridical Approach Method by examining secondary data material as a basis for research, then conducting a search for regulations and literature related to the problem under study. The results of this study indicate that land disputes can be resolved by mediation or out-of-court settlement, the dispute resolution process through mediationis an effort to resolve disputes through negotiation with the help of a neutral third party (mediator) to find a form of settlement that can be agreed upon by the parties or the community in dispute in Gunungsari Village. The result of the dispute resolution process through mediation is an agreement or peace agreement that both have evidentiary value and are binding for the parties. Both do not yet have definite legal force as befits a court decision with permanent legal force. Peace agreements or agreements resulting from outof-court mediation only gain the status of a deed of peace after the parties with the help of a mediator file a lawsuit for peace through the District Cour. Article 36 of PERMA Number 1 Year 2016. Thus, the peace deed has legal certainty and permanent legal force (incracht van gewijsde). Out-of-court dispute resolution through the mediation process needs to be developed to resolve civil disputes. In addition, each court should have certified mediator judges to make it easier for the parties to carry out mediation in court and obtain clear legal certainty such as a peace deed that has permanent legal force from the agreement of the parties to the dispute.